Build Your Confidence : Use mindfulness and meditation to boost self-esteem - Ward, Tara (London : Arcturus, 2020)
Complete just seven steps to unlock the confidence within you. Do you want to discover a way of building up your confidence that's simple and fun? Then this book is a must. The tools and techniques in this book are designed to help you plot out your own path to confidence as you go about your daily life.
"Includes audio meditation."
Keywords: Self-confidence.; Self-esteem.; Mindfulness (Psychology); Psychology